2018
DOI: 10.1002/mc.22877
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in nucleotide excision repair pathway predict survival of esophageal squamous cell cancer patients receiving platinum‐based chemotherapy

Abstract: The benefits of platinum-based chemotherapy (PBC) on survival of esophageal squamous cell carcinoma (ESCC) patients are inexplicit due to the varied therapeutic effects. Nucleotide excision repair (NER) pathway plays a vital role in removing platinum-DNA adducts in tumor cells and hence may modulate the therapeutic effect and survival outcome. The present study assessed the associations of 26 potentially functional regulatory single nucleotide polymorphisms (rSNPs) in nine core NER genes with disease-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Moreover, targeting altered DDR pathways could be an effective way for cancer treatment (4,5). Gene polymorphisms in BER, NER and NHEJ pathway genes have been reported to be related to higher risk of ESCC (12)(13)(14)(15)(16). However, the alterations in DDR pathways, including gene mutations, CNVs, and abnormal expression, are still largely unknown in ESCC, and how alterations in DDR pathways contribute to ESCC needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, targeting altered DDR pathways could be an effective way for cancer treatment (4,5). Gene polymorphisms in BER, NER and NHEJ pathway genes have been reported to be related to higher risk of ESCC (12)(13)(14)(15)(16). However, the alterations in DDR pathways, including gene mutations, CNVs, and abnormal expression, are still largely unknown in ESCC, and how alterations in DDR pathways contribute to ESCC needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants in NER genes were linked to exert an impact on survival outcomes of Chinese ESCC patients (14,15). Moreover, genetic polymorphisms of XRCC6 and XRCC5, two genes in NHEJ pathway, were related to higher risk of ESCC (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNPs in the NER pathway were selected from studies that indicated that SNPs were associated with the risk or prognosis of malignancies in ethnic Chinese [16,18,19,20]. A total of 13 potentially functional SNPs in ERCC5 (rs2094258, rs1047768, rs17655, and rs873601), ERCC2 (rs13181 and rs1799793), ERCC1 (rs735482, rs3212986, and rs11615), XPC (rs2228001 and rs2228000), and XPA (rs1800975 and rs10817938) genes were genotyped using the Sequenom iPLEX MassARRAY system (Sequenom, Inc., San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we conducted a retrospective cohort study to test whether SNPs in genes involved in the NER pathway are associated with prognosis in male patients with OSCC treated with adjuvant CCRT. A total of 13 SNPs in ERCC5 , ERCC2 , ERCC1 , XPC , and XPA genes, which have been found to affect the risk and/or survival of cancers, were selected in the present study [13,14,16,17,18,19,20]. Their associations with clinical outcomes were evaluated using alternative genetic models, including additive, dominant, and recessive models.…”
Section: Introductionmentioning
confidence: 99%